Using web analytics tools to assess the effectiveness of means for promoting library resources - O. M. Udartseva; A. E. Rykhtorova (Библиосфера, 2018)
This article is devoted to analysis of the technologies effectiveness to promote library resources. The first part explores using web analytics and its tools in the library. The study of existing approaches to choose web metrics allows identifying the following key metrics to assess the effectiveness of the library web site operation: (1) attendance metrics; (2) the metrics of involvement and loyalty; (3) social metrics. The techniques effectiveness direct evaluation is proposed to promote library resources based on the analysis of: (1) measurable targeted actions by users on the site; (2) transitions to the library site by external links from search engines; (3) sites with high density of clicks and conversion of site landing pages; (4) existing segments of users and their activity. This paper provides perspectives showing what ways this emerging area of study can help in understanding and improving the perception of products and services on websites of libraries.